SOME SUGGESTIONS FOR FINANCIAL - Hallowes, Craig Brabazon (My University, 2011)
Financial reporting has received structural shocks recently. Many considered opinions have been garnered, and a multitude of laws promulgated, in order to deal with these issues. South African studies of the lessons and proposed solutions are limited. This study solicited the insights of local experts through interviews and questionnaires. It was found that both the internal and the external context of an organisation affect the way people conduct themselves in the assimilation and interpretation of data, that the concept of relevant information is changing, and that the integrity of data can only be improved through a holistic approach to the organisation and the reporting environment. It also found that international standards are regarded as a positive step forward. This research should be of value to professionals and directors managing the integrity of financial information, facilitating organisational communication and deciding what information is most relevant in making investment or business decisions.
MBA - WBS
Keywords: Financial reporting